Audit Lag Perusahaan Sektor Keuangan Dan Non Keuangan Sebelum Dan Saat Covid-19 - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2023)
This study aims to determine whether there are differences in the audit lag of companies engaged in the financial sector and the non-financial sector listed on the IDX (Indonesian Stock Exchange). In addition, this study also aims to find out whether there are differences in the audit lag of companies in the financial, nonfinancial, and all business sectors in the period before the Covid-19 pandemic occurred compared to the period during the Covid-19 pandemic. The sampling method used is non-probability purposive sampling. The number of samples taken using this sampling method were 104 companies engaged in the financial sector and 380 companies engaged in the non-financial sector or 484 companies from all business sectors. Because the data used is not normally distributed, nonparametric statistical tests are used. To test whether there are differences in audit lag between companies in the financial and non-financial sectors both in the period before the Covid-19 pandemic and during the period when the Covid-19 pandemic occurred, the Mann Whitney Test was used. Meanwhile, to test whether there were differences in the audit lag of companies engaged in the financial, nonfinancial, and all business sectors in the period before the Covid-19 pandemic occurred compared to the period when the Covid-19 pandemic occurred, the Wilcoxon Signed Rank Test was used. The results of the study show that there is a significant difference in audit lag between companies engaged in the financial sector compared to companies engaged in the non-financial sector. In addition, the results of the study also show that there are differences in the audit lag of companies engaged in the financial, non-financial, and all business sectors between the period before the Covid-19 pandemic occurred compared to the period during the Covid-19 pandemic.